Recent progress in the racemic and enantioselective synthesis of monofluoroalkene-based dipeptide isosteres - Drouin, Myriam; Paquin, Jean-François (Beilstein Journal of Organic Chemistry, 2017)
Monofluoroalkenes are fluorinated motifs that can be used to replace amide bonds. In order to be incorporated into peptides, it is normally necessary to first synthesize a dipeptide where the amide bond has been replaced with a monofluoroalkene. In that context, this review will present the racemic and enantioselective synthesis of monofluoroalkene-based dipeptide isosteres described since 2007. Some applications of those compounds will also be presented.
Keywords: dipeptide isosteres; monofluoroalkene-based amide bonds; monofluoroalkenes; peptides; synthesis